Integrasi Permainan Engklek dalam Kehidupan Kampus untuk Mengenalkan Budaya Bangsa - Ayu Anggraeni Dyah Purbasari; Afif Amir Amrullah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The influence of global development in the field of technology has caused some younger generations to forget local cultural activities such as behavior, language, and traditional games, which ultimately may lead to a loss of love for the nation and the country. Universitas Pembangunan Nasional Veteran Jakarta is an educational institution with the slogan